Spectroscopic study of the role of alkaline earth oxides in mixed borate glasses - site basicity, polarizability and glass structure - Othman, Hosam; Elkholy, Hagar; Cicconi, Maria Rita; Palles, Dimitrios; de Ligny, Dominique; Kamitsos, Efstratios I.; Möncke, Doris (Journal of Non-Crystalline Solids, 2020)
The effect of alkaline earth ions on the structure and properties of borate glasses near the metaborate composition was studied for two glass series, 30MO-10Li2O-10Al2O3-50B2O3 with M=Mg, Ca, Sr or Ba and xMgO-(30-x)BaO-10Li2O-10Al2O3-50B2O3 series, for undoped and doped (0.5 mol% MnO or CuO) glasses. Thermal and optical properties, including the optical basicity, were correlated with structural variations. IR and Raman spectra showed the highest N4 fraction for the high basicity glasses, decreasing for higher field strength ions (Ba>Sr>Ca>Mg). As determined from far IR bands the mixing of dissimilar cations affects M-O interactions. The glass transition temperature Tg correlates well to the average bond strength of the compared alkaline earth ions. The redox ratio of Mn2+/Mn3+ or Cu2+/Cu+ shifted to lower valences in low basicity glasses. The optical basicity probe ion Mn2+ gives consistently higher values compared to the average optical basicity, suggesting that Mn2+ ions seek out high basicity ligands.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Borate glasses; Force constant; Optical basicity; Raman and IR spectroscopy; Structure property correlation